Risk Prevention and Control Points Through Quantitative Evaluation of Campylobacter in a Large Broiler Slaughterhouse - Zhao, Ge; Huang, Xiumei; Zhao, Jianmei; Liu, Na; Li, Yuehua; Wang, Lin; Gao, Yubin; Wang, Juan; Qu, Zhina; Liu, Junhui; Wang, Junwei (Frontiers in Veterinary Science, 2020)
Chickens contaminated with Campylobacter are a major risk factor for human Campylobacter disease. As a result of the slaughter process, infections should be strictly controlled due to complete exposure of the chickens and the cross-contamination of pathogens. Using @RISK software, quantitative evaluation models of Campylobacter contamination during slaughtering in a large broiler slaughterhouse were constructed. Broiler scalding was set as the starting point of evaluation and four major processes including defeathering, eviscerating, pre-cool rinsing and splitting-transmission were included. Through the simulation of the constructed model, 90% probability of Campylobacter in 100 g chickens after slaughtering were distributed between 0.3~ 50.2 MPN, which was consistent with simulated actual monitoring data 0~16.6 MPN, indicating that the model shows high credibility. In addition, growth curves of Campylobacter during whole slaughtering showed that contamination significantly increased after defeathering, and increased again after pre-cool rinsing. Using correlation coefficients to analyze the sensitivity of each parameter in the model, it was determined that the concentration of Campylobacter in the pre-cool pond water (correlation coefficient: 0.95) was the most critical risk point of sanitary control in this slaughterhouse. In conclusion, this study is the first to incorporate environmental factors during broiler slaughtering into the risk evaluation of Campylobacter contamination, which provides guidance for the sanitary control and risk management of Campylobacter contamination during broiler slaughtering.